Memoirs of a mission : the Ismaili scholar, statesman and poet al-Muʼayyad fil̓-Dīn al-Shīrāzī /: the Ismaili scholar, statesman and poet al-Muʼayyad fil̓-Dīn al-Shīrāzī. (2003) - Unknown
No abstract available